Implementasi Budaya Kerja 5S (Seiri, Seiton, Seiso, Seiketsu Dan Shitsuke) Di Emping Melinjo Ibu Sukati: Indonesia - Marfuah, Hasti Hasanati; Yaning Tri Hapsari; Kurniawanti (UII, 2024)
Emping Melinjo Ibu Sukati is one of the SMEs producing emping in Tegalkenongo, Tirtonirmolo, Kasihan, Bantul. The emping production process is carried out on an untidy production floor, the production equipment used tends to be scattered everywhere, the drying place is not neatly organized. The arrangement of work equipment that is not neatly organized causes workers to take longer to retrieve the production equipment used and affects the productivity level of the workers. The purpose of this service is to provide understanding and assistance in applying the 5S concept to partners so that the production process is more organized and neat. The solution to overcome the existing problems in partners is to use the method of socialization and assistance in implementing the 5S work culture. The term 5S comes from the Japanese language which is known as an abbreviation of: Seiri (Sorting), Seiton (Organizing), Seiso (Cleaning), Seiketsu (Systemize) and Shitsuke (Standardize). The average evaluation result of the implementation of this service is 79.67% so that it can be said that this service is enough to provide understanding for partners and partners are able to apply it in their work. The application of 5S makes the production process run more organized and tidy and the chips produced are more hygienic.